Keeping abreast with long non-coding RNAs in mammary gland development and breast cancer - Hansji, Herah; Leung, Euphemia Y.; Baguley, Bruce C.; Finlay, Graeme J.; Askarian-Amiri, Marjan E. (Frontiers in Genetics, 2014)
The majority of the human genome is transcribed, even though only 2% of transcripts encode proteins. Non-coding transcripts were originally dismissed as evolutionary junk or transcriptional noise, but with the development of whole genome technologies, these ncRNAs are emerging as molecules with vital roles in regulating gene expression. While shorter ncRNAs have been extensively studied, the functional roles of long non-coding RNAs are still being elucidated. Studies over the last decade show that lncRNAs are emerging as new players in a number of diseases including cancer. Potential roles in both oncogenic and tumour suppressive pathways in cancer have been elucidated, but the biological functions of the majority of lncRNAs remain to be identified. Accumulated data are identifying the molecular mechanisms by which lncRNA mediates both structural and functional roles. LncRNA can regulate gene expression at both transcriptional and post-transcriptional levels, including splicing and regulating mRNA processing, transport and translation. Much current research is aimed at elucidating the function of lncRNAs in breast cancer and mammary gland development, and at identifying the cellular processes influenced by lncRNAs. In this paper we review current knowledge of lncRNAs contributing to these processes and present lncRNA as a new paradigm in breast cancer development.